2018
DOI: 10.1097/mpa.0000000000001030
|View full text |Cite
|
Sign up to set email alerts
|

Site-Specific Genomic Alterations in a Well-Differentiated Pancreatic Neuroendocrine Tumor With High-Grade Progression

Abstract: The major categories of pancreatic neuroendocrine tumor (PanNET) are well-differentiated NET and poorly differentiated neuroendocrine carcinoma. Sequencing of these tumors has identified multiple important genes in the pathogenesis of PanNETs, such as DAXX/ATRX, MEN1, TP53, RB, and mTOR pathway genes. We identified a case of well-differentiated PanNET with high-grade progression with simultaneous low- and high-grade histologic regions containing variable genomic profiles. We performed tumor microdissection and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…PNETs are relatively uncommon neoplasms, constituting 1-5% of pancreatic tumors [9,23,24]. Two major categories of PNETs are well-differentiated NETs and poorly-differentiated neuroendocrine carcinomas (NECs) [25].…”
Section: Discussionmentioning
confidence: 99%
“…PNETs are relatively uncommon neoplasms, constituting 1-5% of pancreatic tumors [9,23,24]. Two major categories of PNETs are well-differentiated NETs and poorly-differentiated neuroendocrine carcinomas (NECs) [25].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a PNET tissue biomarker that is able to distinguish LG-PNETs at risk of metastasis from those that are not would enormously benefit appropriate management of this disease. Research has focused on distinguishing GAs that drive the biological behavior of PNETs from those that drive PECAs (18)(19)(20)(21)(22)(23). GAs in genes involved in chromatin remodeling, such as MEN1, DAXX, and ATRX, as well as those in phosphatase and tensin homolog (PTEN) loss, have been found to be enriched in G1, G2, and G3 PNETs, whereas PECAs have been determined to be enriched in GAs that lead to the inactivation of TP53 and/or RB1 and to EMT (5, 19,20,[24][25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Tang LH et al reported 31 well-differentiated PanNETs with a morphologically apparent high-grade component, and did not reveal additional mutations, including TP53 mutations, in the high-grade component [ 46 ]. However, Martin, et al analyzed a PanNET with focal high-grade progression and found an increased CNV and additional mutations in PTEN and SMAD4 only in the high-grade component, suggesting that genetic heterogeneity is seen in rare PanNETs [ 47 ]. Consistent with this study, we have also observed that rare PanNETs with a focal high-grade component can have TP53 mutations in addition to gene mutations commonly present in well-differentiated NETs.…”
Section: Resistance To Molecularly Targeted Therapiesmentioning
confidence: 99%